Impact of Socio-Economic Status in One’s Criminal Behavior: An Assessment: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Socioeconomic status (SES) plays a very important role in individuals and influences everyaspect of human life. Family income, education, employment, unemployment, occupation,family size, and locality of residence are those conditions that impact socioeconomic status toexplain criminal behavior among people. Moreover, others may say that because of theexcessive number of people or number of people living in a family, the cost of living at home isdifficult to sustain. It also encompasses individuals with low educational attainment, lowincome, and unemployment. One of the solutions that we suggest is to increase theemployee’s minimum wage and lower the standards or requirements of work so that morepeople will be employed and they can produce enough and support their needs daily toprevent them from committing a crime.The study reveals that socioeconomic status has an impact, wherein in education, therespondents are spending their time and money cutting classes more than attending classes.As to income, most of the respondents agreed they can save money/ have savings for futurepurposes. In employment, most of the respondents are not interested in their work; they arejust working to provide financially. Also, there are socioeconomic conditions that contribute tocriminal behavior, such as unemployment and the high qualifications or requirements forfinding a job, which is why most of the respondents are having difficulties finding a job. Forincome level, the respondents can provide their daily needs finances, especially for schoolexpenses. And lastly, regarding prevalent levels of unemployment, the responses were thatthey are undecided if they want to work or not.The researchers recommend an assessment guide to give information about the impact ofsocioeconomic status on one’s criminal behavior. This is done in collaboration with officials ofBarangay Gaya-gaya and LGU for dissemination of information through flyers, brochures,seminars, and workshops. And through the use of social media platforms to help with thedissemination of information regarding the study.
Keywords: Criminology